Enhancement of Upconverted Fluorescence by Interference Layers. Issue 6 (2nd December 2016) - Wirth, Janina; Green, Kory K.; O'Connor, Megan; Lim, Shuang F.
Abstract : Upconverting nanoparticles show potential applications in the field of photovoltaics and array‐based detection devices. While fluorescence enhancement using interference of incident radiation is well known in Stokes‐shift type systems such as fluorescent dyes; the effect of such interference geometry in nonlinear Anti‐Stokes type emission, such as in upconversion rare earth photophysics is demonstrated for the first time. This work describes in detail the influence of the interference modulation on both the excitation (interion energy transfer) and radiative decay with nonradiative decay processes active between emissive levels. These effects are illustrated in the thickness dependence of the decay rate and rise time. Single particle upconverted spectra and time‐resolved measurements show concurrent optimization of the infrared absorption and emission at 540 and 650 nm, with an average enhanced emission of 20 times at λ = 540 and 45 times at λ = 650 nm, dependent on the interference layer thickness and on the excitation intensity. The experimental results are correlated with finite element modeling. Both experiments and calculations show emission enhancement at an interference layer thickness of about 740 ± 20 nm, where such tolerance and the planar design, leads to ease in implementation in applications. Abstract : A new approach of enhanced upconversion luminescence by the interference modulation of the infrared excitation and visible emission wavelengths of single particles is presented. By the positioning of NaYF4 nanocrystals codoped with Yb 3+/ Er 3+ ions above a reflecting gold surface at controlled distances enhancements of up to 45 times at a wavelength of 650 nm can be achieved.